2010
DOI: 10.1111/j.1365-2672.2009.04416.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and survival of Salmonella Typhimurium and human adenovirus from spiked sewage sludge applied to soil columns

Abstract: Aims:  This study investigated the survival and transport of sewage sludge‐borne pathogenic organisms in soils. Methods and Results:  Undisturbed soil cores were treated with Salmonella enterica ssp. enterica serovar Typhimurium‐lux (STM‐lux) and human adenovirus (HAdV)‐spiked sewage sludge. Following an artificial rainfall event, these pathogens were analysed in the leachate and soil sampled from different depths (0–5 cm, 5–10 cm and 10–20 cm) after 24 h, 1 and 2 months. Significantly more STM‐lux and HAdV le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…According to a study [44] conducted on modeling, the exposures and risks to humans from pathogens potentially present on crops which have been grown on land treated with sewage sludge concluded that risk of microbial exposure is remote. However, organic matter in sewage sludge may influence the transport and survival of bacterial pathogens and the strong soil adsorption may rule out virus contamination possibilities [45]. Since sludge is a source of heavy metals and other toxic organic compounds, careful monitoring and characterization of sewage sludge are inevitable for such microbial valorization trials.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study [44] conducted on modeling, the exposures and risks to humans from pathogens potentially present on crops which have been grown on land treated with sewage sludge concluded that risk of microbial exposure is remote. However, organic matter in sewage sludge may influence the transport and survival of bacterial pathogens and the strong soil adsorption may rule out virus contamination possibilities [45]. Since sludge is a source of heavy metals and other toxic organic compounds, careful monitoring and characterization of sewage sludge are inevitable for such microbial valorization trials.…”
Section: Discussionmentioning
confidence: 99%
“…Leaching of Salmonella through soil was observed to reach greater depths after application of slurry than of manure [44]. In the same line, the application method of fertilizers can also have an efect on Salmonella survival in soil since an injection of manure or slurry or clumping of the applied fertilizer aboveground protect bacteria in the soil from desiccation, UV, and high temperatures [43,45,46]. Agricultural practices like tillage that have an efect on the porosity of soil determine the extent of leaching [47] and the availability of oxygen.…”
Section: Current Topics In Salmonella and Salmonellosis 174mentioning
confidence: 93%
“…Transport and survival of bacterial pathogens in soil is also inluenced by amendment of fertilizers probably because of the presence of organic mater [43]. Leaching of Salmonella through soil was observed to reach greater depths after application of slurry than of manure [44].…”
Section: Current Topics In Salmonella and Salmonellosis 174mentioning
confidence: 99%
“…As shown in Tables 4 and 5, viral concentrations vary widely in environmental samples, and Tables 3 and 4 demonstrate the variability in host faecal and wastewater. Therefore, detection of these markers in environmental waters can be difficult due to factors such as dilution, sorption to particulate matters, environmental persistence, loss due to recovery and DNA extraction, and the fact that only a small volume of DNA sample is used for PCR/qPCR analysis (Horswell et al, 2010;Wong et al, 2012). It is therefore, recommended that a "toolbox" approach should be used for the accurate identification of polluting source(s) (Noble et al, 2006;Ahmed et al, 2012;Mauffret et al, 2012).…”
Section: Concentrations Of Viral Mst Markers In the Water Environmentmentioning
confidence: 99%